Effects of a carbohydrate-electrolyte solution on cognitive performance following exercise-induced hyperthermia in humans - Lee, Jason KW (2015)
Background: There is limited information on the effects of sports drinks on cognitive function after exercise in the heat. We aimed to investigate the effects of ingesting a commercially available carbohydrate-electrolyte (CHO) solution on cognitive performance following exercise-induced hyperthermia. Methods: Twelve participants completed three practices of cognitive tests, one full familiarisation and two experimental trials in an environmental chamber (dry bulb temperature: 30.2 ± 0.3°C, relative humidity: 70 ± 3%). The experimental trials consisted of five cognitive tests (symbol digit matching, search and memory, digit span, choice reaction time and psychomotor vigilance test) performed before and after a 75-min run on a treadmill at 70% VO2 max. One ml/kg body mass of a 6.8% CHO solution or placebo was consumed at the start, every 15 min during exercise and between cognitive tests after exercise. Core temperature, heart rate, blood glucose concentrations, subjective ratings and cognitive performance were assessed (symbol digit matching, search and memory, digit span, choice reaction time and psychomotor vigilance). Results: Participants were hyperthermic at the end of the run (placebo: 39.5 ± 0.4°C, CHO: 39.6 ± 0.5°C; Mean ± SD; p = 0.37). The change in blood glucose was higher with CHO ingestion (1.6, 0.7 to 4.5 mmol/L) (median, range) than with placebo ingestion (0.9, -0.1 to 4.7 mmol/L; p < 0.05). CHO ingestion reduced the maximum span of digits memorized, in contrast to an increase in maximum span with placebo ingestion (p < 0.05). CHO solution had no effect on other cognitive tests (p > 0.05). Conclusions: These results suggest that CHO solution ingestion may impair short-term memory following exertional heat stress.